PENINGKATAN EFISIENSI PENGGUNAAN BORON DALAM OPTIMASI PRODUKSI JAGUNG MANIS DI LAHAN KERING - Nugroho, Gabryna Auliya; Hidayat, Muhamad Taufiq; Albarki, Georona Kusma; Siswanto; Natajaya, Andrean; Kurniawan, Syahrul (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
The range between boron deficiency and toxicity in plants is utterly narrow, so that the certain dose of boron fertilizer is required for plants. Indicators of optimum boron fertilization can be measured from plant production and boron use efficiency (BUE) value. BUE influenced by the amount of soluble B-soil, type of B fertilizer, amount of boron input, type of plant, and adequacy of available macronutrients (NPK). However, excessive application of NPK base fertilizer from inorganic fertilizers can trigger soil degradation. Currently, there has not been much research that measures the reduction in the dose of NPK base fertilizer combined with boron fertilizer on plant BUE. The combination of reducing the dose of NPK base fertilizer and boron fertilizer was tested on sweet corn plants on production and BUE. This study was conducted with a randomized block design with 7 treatments, namely without fertilization (K0), base fertilization (D1), 100% base fertilization and 50–15% borate (D2–D4), and 75% base fertilization and 50–15% borate (D5–D7). The results of the initial soil analysis showed low boron content in the soil, so borate fertilization was required to provide nutrients for sweet corn plants. Application of NPK base fertilizer (100%) and addition of borate fertilizer at a dose of 50-100% ( 3-6 kg/ha) significantly increased growth, plant biomass, B uptake, boron recovery efficiency (BRE), and B fertilizer efficiency ratio, compared to lower NPK-base fertilizer. Based on the estimated response curve, the recommended dose to achieve optimum-maximum sweet corn production and maximum boron recovery efficiency is 100% macro inorganic fertilization (urea, SP-36, KCl) combined with 5.72-6.75 kg/ha borate fertilizer.